A European system to improve machinery safety by drawing on user's experience : summary of a seminar - Boy, Stefano (Brussels, 2006)
"This publication summarises the results of a seminar (27 March 2006, Brussels), organised by ETUI-REHS to unveil its strategy for improving machinery standards through users' feedback. Under the chairmanship of Bart Samyn, Deputy General Secretary of the European Metalworkers' Federation (EMF), the five ETUI-REHS national partners - Finland, France, Germany, Italy, United Kingdom - presented the main findings of a project on forklift trucks (FLTs), together with a selection of design issues arising directly out of users' experience.